Growth of CaHPO4 Crystals in Silica Gel Media and Its Characterization Studies, Nucleation Reduction Process - SUNDARAMOORTHI, P.; KALAINATHAN, S. (Asian Journal of Chemistry, 2010)
The calcium hydrogen phosphate crystals were grown in sodium meta silicate gel media. The growth processes were done by single diffusion method for different physical and chemical parameters. In the present investigation, calcium hydrogen phosphate crystals optimum growth parameters were identified. The sunlight exposure medium of growth gave better nucleation reduction. The grown crystals were analyzed by XRD, FTIR, TGA, SEM, AAS and etching.